Using online technology for hotel presentation - Gajdoš, Martin; Postler, Milan, 1960-; Javornický, Peter; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2009)
The thesis is devoted to describing the current on-line marketing opportunities and their application for the newly emerging hotel. The goal was to describe current technologies and suggest how to use them in hotels Moods.
Vedoucí práce: Milan Postler
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Způsob přístupu: Internet
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2010
Rok obhajoby 2010
Keywords: informační management [obor dipl. práce]; marketing; diplomové práce; marketing; master's theses